(untitled) - Geschäftsführender Herausgeber: Prof. Dr. Tobias Wolbring; Prof. Dr. Eva Barlösius; Prof. Dr. Monika Jungbauer-Gans; Prof. Dr. Malte Reichelt; Prof. Dr. Christian von Scheve; Prof. Dr. Daniela Schiek; Prof. Dr. Roland Verwiebe (SozW Soziale Welt, 2004)
Soziale Welt is one of the important journals within German sociology and is even read in foreign countries. It includes empirical and theoretical contributions from all areas of the subject and tries to portray the development of sociology and to give a new impetus. In addition to the quarterly published issues, there are special issues with a unified theme. The journal "Soziale Welt" is aimed at sociologists, social scientists, and at generally interested readers. Website: www.soziale-welt.de